2013
DOI: 10.5296/jbls.v4i2.3043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Level on Growth Performance, Carcass Composition and Survival Rate of Fry Monosex Nile Tilapia, Oreochromis niloticus Reared under Re-circulating System

Abstract: Fry monosex Nile tilapia (Oreochromis niloticus) were fed in five dietary protein levels (21%, 25%, 32% 37% and 45%) to investigate casual effects on growth performance, carcass composition and survival rate. Tests were carried out in 10 glass tank (50 x 25 x 40 cm) containers (50 L) of reticulating system maintained at 30 ± 1°C. At the beginning of tests, one hundred tilapia fry were randomly divided into five different groups with two replicates. Diets were fed to duplicate groups of ten fry with an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
2
2
0
2
Order By: Relevance
“…The present study observed significantly higher FBW, WG, SGR and FER in yellow drum fed the Mix diet than the FO group (p < .05), similar to the result reported in Nile tilapia (O. niloticus), in which the best growth rate and SGR were obtained in fish fed the diet containing a mixture of vegetable oils in equal proportions (Sagne et al, 2013).…”
Section: Growth Performance Body Composition and Fatty Acid Compositionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study observed significantly higher FBW, WG, SGR and FER in yellow drum fed the Mix diet than the FO group (p < .05), similar to the result reported in Nile tilapia (O. niloticus), in which the best growth rate and SGR were obtained in fish fed the diet containing a mixture of vegetable oils in equal proportions (Sagne et al, 2013).…”
Section: Growth Performance Body Composition and Fatty Acid Compositionsupporting
confidence: 90%
“…Interestingly, the blend inclusion of the terrestrial lipid was reported to increase dietary fatty acid profile (Dominique, Katheline, & Andrew, 2008) that enhanced palatability (Yu, Sinnhuber, & Putnam, 1977), feed intake (Kim et al, 2012) and growth to several cultured fish species: Nile tilapia (Oreochromis niloticus) (El-Hammady & Saad, 2014), olive flounder (Paralichthys olivaceus) (Kim et al, 2012), gilthead seabream (S. aurata) (Wassef, Saleh, & El-Abd El-Hady, 2009) and rainbow trout (Oncorhynchus mykiss) (Kutluyer et al, 2017;Sagne et al, 2013). Meanwhile, linseed oil and lard are among the terrestrial lipid ingredients available to replace fish oil in the formulated diets (Huang et al, 2014;Zhou et al, 2015).…”
mentioning
confidence: 99%
“…Timbangan yang digunakan adalah timbangan digital (ketelitian 0,1 g), sedangkan panjang diukur menggunakan penggaris aluminium (ketelitian 0,1 cm). Parameter pertumbuhan dihitung menurut Loum et al (2013); pertumbuhan bobot mutlak (PBM) dihitung dengan rumus Bt-B0, di mana Bt = bobot rata-rata ikan pada saat akhir (g), B0 = bobot rata-rata ikan pada saat awal (g), dan laju pertumbuhan bobot harian (LPH) (%/hari) dihitung menggunakan persamaan {Ln Bt-Ln Bo)/t}×100, di mana t = lama waktu pemeliharaan (hari).…”
Section: Uji Pertumbuhanunclassified
“…Lipid body content increased significantly with high dietary protein levels from 21.88% to 45.50%. The carcass crude lipid was recorded as higher (9.4%) in the fry fed on diet containing 45.50% protein, followed by fish fed on diet having protein 21.88% [55].…”
Section: Chemical Composition Of Fish Fleshmentioning
confidence: 91%